Avian species abundance and habitat association in Makurdi metropolis, Benue State, Nigeria (2022)
Appraisal of avian species, especially in urban areas, is paramount to determining the health of the environment. The research focused on the abundance, diversity, and habitat association of avian species within and around the new bridge in Makurdi metropolis, Benue State, Nigeria. The habitats selected were: Abattoir (Ab), Oxbow Lake (Ol), and Farmland (Fl). A line transect length of 100 m was laid (1 at Ab, 2 each at Ol and Fl). The line transect method was used to identify and estimate the abundance and diversity of birds (at 06:00–09:00 hrs and 15:00– 18:00 hrs) aided with binoculars for 2 consecutive days weekly in June–November 2021. The Textbook on Birds of West Africa was used for the identification of the species. The dataset was analyzed using descriptive statistics and diversity indices. The result revealed a total number of 23 species (4061 individuals) belonging to 15 families. Five species (41 individuals), 19 species (2,804 individuals), and 8 species (1,216 individuals) were recorded at Abattoir, Oxbowlake, and Farmland, respectively. Ploceus cucullatus (55.68%) was the most abundant species, while Accipitridae (12.5%) was the dominant family recorded. Variation in density varies across the habitat, with farmland (723.13) being the densest area. The diversity indices indicated that farmland (D: 0.668, H1: 1.571, and richness (2.267)) had a high value when compared to other habitats. Conservation and management of urban avian species should be encouraged to promote avi-tourism.